Heme oxygenase-1 alleviates cigarette smoke-induced restenosis after vascular angioplasty by attenuating inflammation in rat model. (14th March 2016) - Ni, Leng; Wang, Zhanqi; Yang, Genhuan; Li, Tianjia; Liu, Xinnong; Liu, Changwei
Highlights: We established balloon-induced carotid artery injury model of rats that were exposed to cigarette smoke. Smoke exposed rats manifested higher level of inflammatory cells infiltration, inflammatory cytokines expression and neointimal hyperplasia than comparison. Hemin alleviates infiltration of inflammatory cells, decreases the level of inflammatory reaction and elevates HO-1 in carotid arteries of smoking rats. Hemin inhibits neointimal formation after balloon injury in smoking rats Abstract: Cigarette smoke is not only a profound independent risk factor of atherosclerosis, but also aggravates restenosis after vascular angioplasty. Heme oxygenase-1 (HO-1) is an endogenous antioxidant and cytoprotective enzyme. In this study, we investigated whether HO-1 upregulating by hemin, a potent HO-1 inducer, can protect against cigarette smoke-induced restenosis in rat's carotid arteries after balloon injury. Results showed that cigarette smoke exposure aggravated stenosis of the lumen, promoted infiltration of inflammatory cells, and induced expression of inflammatory cytokines and adhesion molecules after balloon-induced carotid artery injury. HO-1 upregulating by hemin treatment reduced these effects of cigarette smoke, whereas the beneficial effects were abolished in the presence of Zincprotoporphyrin IX, an HO-1 inhibitor. To conclude, hemin has potential therapeutic applications in the restenosis prevention after the smokers' vascular angioplasty.